Strategi Guru Pendidikan Agama Islam Memotivasi Siswa Dalam Meningkatkan Pengamalan Keagamaan - andrianto, andrianto; Hidayatullah, Rully; Sumiarti, Sumiarti; Noviyani, Rafiqa; Nofitayanti, Nofitayanti (Journal Education And Islamic Studies, 2023)
This research was motivated by the lack of religious practice by MTsN 1 Head of Hilalang students, especially in the practice of fardhu prayers, reading the Al-Qur'an and giving alms. This research aims to determine the strategies of Islamic Religious Education teachers as motivators in increasing the practice of fardhu prayers, reading the Al-Qur'an and fostering students' interest in giving infaq at MTsN 1 Head of Hilalang. The research method used is a qualitative method. The research data sources are Madrasah Principals, PAI Teachers and students. The data collection tools that the author uses are observation, interviews and documentation. To analyze data is data reduction, data presentation and drawing conclusions. The results of the research are (1) The strategy of Islamic Religious Education teachers as a motivator in increasing the practice of fardhu prayers for students at MTsN 1 Head of Hilalang, Padang Pariaman Regency has been going well but is not optimal because there are still students who are reluctant to practice fardhu prayers. (2) The Islamic Religious Education teacher's strategy as a motivator in increasing students' practice of reading the Al-Qur'an has also gone well but is also not optimal, because there are still students who do not want to read the Al-Qur'an. (3) The teacher's strategy for Islamic Religious Education as a motivator in growing students' interest in giving infaq has been implemented well by the teacher, students already have an interest in giving infaq to people in need.